2023
DOI: 10.1037/mac0000083
|View full text |Cite
|
Sign up to set email alerts
|

User-generated digital flashcards yield better learning than premade flashcards.

Abstract: Digital flashcard users typically must choose between creating their own flashcard content or using freely available flashcard sets. The latter is more convenient and saves time, but is it more effective for learning? We conducted six experiments, each involving the use of user-generated or premade flashcards to learn material drawn from educational text passages, followed by a 48-hr delayed criterial test. Different approaches to generating content and variations in the quality of premade content were also ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…If instructors did not assign course credit, usage rates would likely be significantly lower than observed in our experiments (Maurer & Shipp, 2021, but also see J. L. Janes et al, 2018, for higher rates of self-regulated successive relearning). Instructors could also consider encouraging students to create their own digital flashcards (which can be even more effective than premade flashcards, Pan et al, 2022). In summary, instructors could help students engage in successive relearning in many different ways.…”
Section: Considerations For Instructorsmentioning
confidence: 99%
“…If instructors did not assign course credit, usage rates would likely be significantly lower than observed in our experiments (Maurer & Shipp, 2021, but also see J. L. Janes et al, 2018, for higher rates of self-regulated successive relearning). Instructors could also consider encouraging students to create their own digital flashcards (which can be even more effective than premade flashcards, Pan et al, 2022). In summary, instructors could help students engage in successive relearning in many different ways.…”
Section: Considerations For Instructorsmentioning
confidence: 99%
“…Another research results (Lailatul Muflikha, 2018) showed that Flashcards study on improving students' writing skills and improving student learning responses is quite good. Pan et al, (2022) suggested that generating one's own flashcards enabled productive learning processes that enhanced memory and comprehension.…”
Section: Introductionmentioning
confidence: 99%